Management of the Life Cycle of Digital Library Materials - Deegan, Marilyn (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2001)
This paper does not deal in any detail with digital preservation, rather it examines the development of digital content and digital libraries in the broader content of digital developments and library developments. Implicit throughout this is the need to create or acquire digital content for long-term access, which means that preservation needs must be foregrounded at all stages of the digital lifecycle.